Children and adolescents with severe acute behavioural disturbance in the emergency department. (28th April 2020) - Carison, Anna; Babl, Franz E; Hill, Ashley; O'Donnell, Sinead M
Abstract: Objective: Mental health (MH) presentations to ED are increasing in children and adolescents. Little is known about patients with severe acute behavioural disturbance (ABD). We set out to describe patients with ABD severe enough to trigger an acute crisis team response in ED (termed 'Code Grey') and how they differ from other MH patients. Methods: Retrospective electronic medical record review of all ED patients with MH discharge codes at a tertiary children's hospital. We assessed the epidemiology and management of patients who triggered acute crisis team interventions (Code Grey) as proxy for severe ABD. We calculated the odds ratios (ORs with 95% confidence intervals) of key demographic factors compared to other MH patients. Results: During 2018, there were 85 347 ED presentations of which 1695 (2.0%) were related to MH diagnoses; 84 MH patients had 141 MH presentations triggering 204 Code Greys (26 patients triggered 59% of Code Greys). These patients had higher triage acuity (OR 12.6 [8.3–19.0]), stayed longer in ED (>12 h OR 8.2 [5.1–13.1]) and were more likely to be admitted (OR 2.0 [1.4–3.0]) compared with non‐Code Grey MH presentations. Patients were physically (19.2%), mechanically (31.9%) or chemically restrained (37.6%). Eight different medication approaches were used as either a single agent or a combination of oral and/or intramuscular agents. Conclusions: Children and adolescents with severe ABD differ from other MH presentations and often require physical or chemical restraint. Anticipatory management plans may be valuable for repeat presenters. Abstract : Severe acute behavioural disturbance in children and adolescents in the ED, regardless of underlying cause, can be a major management challenge.